Assessment of potentially toxic element pollution in soils and related health risks in 271 cities across China. (1st February 2021) - Hu, Bifeng; Shao, Shuai; Ni, Hao; Fu, Zhiyi; Huang, Mingxiang; Chen, Qiuxiao; Shi, Zhou
Abstract: Potentially toxic element (PTE) pollution has been extensively studied at a local and regional scale in China. However, further research needs to be conducted at a national level. To this end, in current study we systematically compiled data of around 170, 000 soil samples collected from 1153 papers published between 2008 and 2018. Based on these data we conducted a comprehensive analysis on the pollution status, pollution hotspots, and potential dominant sources of PTEs (As, Cd, Cr, Cu, Hg, Pb, Ni and Zn) in soils in 271 cities of China using geochemical accumulation index, potential ecological risk index, health risk evaluation model, univariate local Moran's I index, and bivariate local Moran's I index. Our results indicated an obvious accumulation of PTEs in the soils of most cities. In addition, the contents of Cd, Hg, Pb, and Ni were higher in China when compared to other several countries under comparison. Pollution hotspots of PTE and hotspots of human health risks may occur due to PTE exposure were mainly distributed in South (S) and Southwest (SW) of China. Cities with PTEs accumulation in soil due to industrial activities were mainly located in East (E) and North (N) China. Cities that had high concentrations of PTE due to agricultural activities were mainly located in central and Northeast (NE) China. Most cities with an accumulation of PTEs in soils primarily due to mining activities were found in West (W) and Northwest (N) China. Cities with PTEs mainly sourced from soil parental material were distributed in Southwest (SW) China. This study provides comprehensive and specific information and valuable implications for developing advanced scientific and efficient strategies to prevent and control PTE pollution the soils in China. Graphical abstract: Image 1 Highlights: An obvious accumulation of PTEs was detected in the soils of most cities in China. Cd and Hg were confirmed as most seriously polluted elements in soil in China. Contents of Cd, Hg, Pb, and Ni were higher in China as compared to other countries. Residents in south and southwest China suffer greater human health risk. Dominant sources of PTEs in soil in different cities in China were identified. Abstract : Different sources which contributed potentially toxic element accumulation in different cities in China were identified in this study.